2023
DOI: 10.3390/ijms24043423
|View full text |Cite
|
Sign up to set email alerts
|

Viruses Binding to Host Receptors Interacts with Autophagy

Abstract: Viruses must cross the plasma membrane to infect cells, making them eager to overcome this barrier in order to replicate in hosts. They bind to cell surface receptors as the first step of initiating entry. Viruses can use several surface molecules that allow them to evade defense mechanisms. Various mechanisms are stimulated to defend against viruses upon their entry into cells. Autophagy, one of the defense systems, degrades cellular components to maintain homeostasis. The presence of viruses in the cytosol r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 160 publications
0
5
0
Order By: Relevance
“…Yang discussed autophagic regulation during the viral binding to cell surface receptors [16]. A virus binds to its specific receptors to infect cells.…”
mentioning
confidence: 99%
“…Yang discussed autophagic regulation during the viral binding to cell surface receptors [16]. A virus binds to its specific receptors to infect cells.…”
mentioning
confidence: 99%
“…It has been shown that autophagy regulates integrin-mediated cell adhesion and may promote cell migration affecting the turnover of focal adhesions [48,49]. Interestingly, integrins may also play an important role in the autophagosome formation by direct interactions with LC3 proteins [50,51]. We speculate that EVs can affect bidirectional interplay between integrin recycling and autophagy thereby promoting remodeling of focal adhesions and microglial motility.…”
Section: It Has Been Shown That Activation Of Autophagy Can Promote N...mentioning
confidence: 80%
“…Viral infections affect the membrane components of cells in various ways, depending on the specific virus and the host cell type [17,63]. Viruses interact with cell surface receptors, membrane proteins, and lipids to facilitate entry into the host cell and promote viral replication [28,[64][65][66]. For example, the spike protein of SARS-CoV-2 facilitates virus entry into host cells by interacting with the ACE2 receptor on the cell membrane [67].…”
Section: Viral Manipulation and Interaction With Host Cell Membranementioning
confidence: 99%
“…Furthermore, the impact of viral infection in host cells extends to other cellular structures and processes, such as autophagosomes and lysosomes [27,28]. These organelles play crucial roles in cellular homeostasis, protein synthesis, and degradation [29,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation